The Effect of a Combination of Ethanol Extract from Leaves and Flowers of Plumeria acuminate L. Against Aedes aegypti Larvae - Martha Indah Widiyaningtiyas; Rizky Ardinansyah Putra; Evy Ratnasari Ekawati; Dheasy Herawati; Arifa Mustika (Journal of Multidisciplinary Applied Natural Science, 2025)
Aedes aegypti is the primary vector that causes dengue virus (DENV) infection. Ae. aegypti resistance to abate (Temephos) has occurred in Indonesia and several other countries. Innovations are needed to develop alternative ingredients that can be used as natural larvacides. The Plumeria acuminate L. is an Indonesian plant with metabolites that have the potential to act as larvicides. This study aims to determine the potential combination of ethanol extract of P. acuminate L. leaves and flowers as a larvicide for A. aegypti. A laboratory experimental study with a post-test-only control group design was carried out on Ae. aegypti larvae instar III. The larvicide test was carried out according to WHO standards in 2005 with concentrations of 10000, 7500, 5000, and 2500 ppm, as well as control (water and 1% DMSO), with 20 larvae for each concentration. The observation was carried out at the 24th and 48th hours with 3 repetitions. Larval mortality data was analyzed using one-way ANOVA statistical tests to determine significant differences and lethal concentrations (LC50 and LC90) were calculated using probit analysis using SPSS software. The mortality of Ae. aegypti larvae due to the administration of a combined ethanolic extract of P. acuminate L. leaves and flowers was the highest at doses of 10000 and 7500 ppm, which was 100% with lethal concentrations of LC50 and LC90 of 3364.715 and 6293.759 ppm at the 24th hour observation, whereas at the 48th-hour observation, lethal concentrations were detected at 1767.998 and 2941.138 ppm, respectively. One-way ANOVA analysis test showed a significant difference in Ae. aegypti larval mortality due to the administration of a combined ethanol extract of P. acuminate L. leaves and flowers at 24th-hour observation (p = 0.000) and (p = 0.013) at 48th hour observation. The combination of ethanol extract of P. acuminate L. leaves and flowers showed larvicidal activity against Ae. aegypti larvae as evidenced by larvae mortality which were influenced by concentration and observation time.